Probing the Conformational Diversity of Cancer‐Associated Mutations in p53 with Ion‐Mobility Mass Spectrometry1. Issue 16 (14th March 2013) - Jurneczko, Ewa; Cruickshank, Faye; Porrini, Massimiliano; Clarke, David J.; Campuzano, Iain D. G.; Morris, Michael; Nikolova, Penka V.; Barran, Perdita E.
<x xml:space="preserve">Abstract</x> Conformational flexibility: The DNA‐binding domain of tumor suppressor protein p53 (see picture) is characterized by using ion‐mobility mass spectrometry. Wild‐type p53 and common single‐point carcinogenic mutations exhibit diverse conformational states upon transfer into a solvent‐free environment of the mass spectrometer. DNA‐binding properties of wild‐type p53 and an engineered second‐site suppressor mutation H115N were also investigated.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>